Silver souls - Vinson, Susan (Glen Waverley, Victoria : Sid Harta Publishers, 2018)
"Lisa, an Australian girl on holidays with her parents in Chile, makes friends with a local girl named Ximena who is no ordinary girl because her best friends are dolphins! Together, the two girls form an incredible bond with the sea and the dolphins while facing great dangers. Dive into the water and share a fantastic adventure with these magical creatures. Set amongst the beautiful scenery of Chile, ancient home of the Incas, this is a story of friendship, courage, love and the magic of life."--Back cover.
Keywords: Australian fiction -- 21st century; Teenage girls -- Juvenile fiction; Dolphins -- Juvenile fiction; Chile -- Juvenile fiction; Australian